Analisis penerapan penatausahaan barang milik negara pada Kantor Pencarian dan Pertolongan Kelas A Sorong Papua Barat Daya menurut Peraturan Menteri Keuangan No. 181 Tahun 2016 - Sigarlaki, Januarius Yani; Kalangi, Lintje; Wokas, Heince R. N. (Riset Akuntansi dan Portofolio Investasi, 2025)
State property management includes accounting, inventory and reporting. The purpose of this study is to determine whether the government property management at Sorong Class A Search and Relief Office is in accordance with the regulations governing government property management. This research is qualitative descriptive and the data used in this study are primary data obtained from sources or informants and secondary data obtained from literature. The Class A Search and Relief Office of Sorong, Southwest Papua has prepared the state property administration according to the Minister of Finance Regulation No. 181 of 2016. However, there are still problems in the preparation of the State Property Administration because the labeling of all physical assets has not been completed.